Viral IL-10 can promote the proliferation, migration and invasion of nasopharyngeal carcinoma cells and inhibit their apoptosis - Qin Qiu; Xingyu Yang; Xiaojiang Li; Yanxin Ren; Ning Huang (Discover Oncology)
Abstract Purpose Nasopharyngeal carcinoma is a common clinical malignant tumour in the nasopharynx. The secretion of vIL-10 by EB virus can promote the development of nasopharyngeal carcinoma. The purpose of this study was to provide a theoretical basis for potential targets and mechanisms of vIL-10 in nasopharyngeal carcinoma. Methods A total of 100 ng/mL vIL-10 was applied to the nasopharyngeal carcinoma CNE-2 cell line for 48 h, and then whole transcriptome sequencing analysis was performed to identify potential targets and signalling pathways of vIL-10 in nasopharyngeal carcinoma. The effects of vIL-10 on the proliferation, migration, invasion and apoptosis of human nasopharyngeal carcinoma cells were determined by ELISA, Ki67 immunofluorescence, colony formation, transwell migration/invasion, Hoechst 33,258 staining, flow cytometry and other experiments, and the potential effects of vIL-10 on nasopharyngeal carcinoma cells were verified at the cellular level. Western blotting was performed to measure the changes in key factors of the JAK1-STAT3 signalling pathway in nasopharyngeal carcinoma cells after vIL-10 treatment. Results The whole transcriptome gene sequencing results showed that vIL-10 could effectively activate the JAK-STAT signalling pathway and upregulate the expression of JAK1 and STAT3. Moreover, vIL-10 inhibited the apoptosis of nasopharyngeal carcinoma cells, enhanced their migration and invasion capabilities, and further promoted the proliferation of nasopharyngeal carcinoma cells. Conclusion vIL-10 regulates the JAK1-STAT3 signalling pathway, promotes the proliferation of NPC cells, enhances their migration and invasion capabilities, inhibits tumour cell apoptosis, and participates in the progression of nasopharyngeal carcinoma.